Xanthan gum production via ultrafiltration using hydrolyzed molasses, with fructose as by-product a plant design - Azurin, Erika Claire J.; Novilla, Joseph Onyl S.; Tumamao, Jesusa Marie DT.; Yap, Kristian July R. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
A new process technology in the production of xanthan gum is presented in the study. It aims to lower the usual cost of production of xanthan by employing new processes, and by exploring possible alternative raw materials. In this study, the production utilizes sugarcane molasses as a new material, and involves new processes such as hydrolysis and chromatographic technology for the separation of the desired molasses component, and ultrafiltration in concentration the broth. This innovation leads to the formation of a by-product, fructose, which can also be sold in the market.The market study of xanthan gum has established that the local market has sufficient demand; however, at present, there is no known manufacturing plant operating here in the Philippines. Most of the xanthan gum is imported from the countries, especially from France. This aspect has been the motivation of the study. Since the demand for food-grade xanthan gum is predicted to increase at approximately 5% per year, a local manufacturing plant which will supply the local market is rather advantageous to the Food Industry. The plant is proposed to be built in Calaca, Batangas, near the source of sugarcane molasses. The prices of xanthan gum and fructose are Php 400 and Php 200 per kg, respectively. Thirty percent of the xanthan gum local demand and 14.5 percent of the fructose annual demand is prospected to be provided for by the plant. The plant is expected to produce 176,951 kg/year xanthan gum and 402,554 kg fructose/year, and will run for 15 years.The fixed capital cost amounted to Php 69,054,430.17 and the total product is equal to Php 44,591,282.08. The plant will operate 24 hours, with two 8-hours shifts. All the engineers will have a monthly salary of Php 40,000 and all the personnel, including the technicians and laborers, will receive minimum daily wage of Php 291.The profitability analysis came up with a payback period of 1.83 years and a rate of return equal to 54.53 percent. The MARR was set to 24 percent, corresponding to the maximum risk for a new process technology. The plant is considered profitable after comparing the MARR to the obtained IRR at 53.78 percent.With revenue equal to Php 151,289,802, te break-even point of the production is at 31.97 capacity. It has a monetary value of Php 74,101,430. To ensure profit, a production rate of no less than 86,668 kg xanthan gum per year and 197,170 kg fructose per year should be achieved. The plant will shut down if it produces 72,465 kg xanthan gum per year and 164,858 kg fructose per year, or less, which corresponds to 26.73 percent of the plant capacity.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Xanthan gum